Don’t forget the exogenous microbial transglutaminases: it is immunogenic and potentially pathogenic - Aaron Lerner; Torsten Matthias (AIMS Biophysics, 2016)
The exogenous microbial transglutaminase that imitates extensively the functions of the endogenous transglutaminases, is a universal protein cross-linker and translational modifier of peptides. The intestinal microbiome, dysbiome, pathobiome, probiotics and industrial processed food are at the origin of the luminal microbial transglutaminase daily cargo. It is hypothesized that those exogenous enzymes, are potential drivers of neurodegenerative and neuroinflammatory diseases via the gut luminal eco events. The substantial luminal activity of the enzyme, by cross-linking naive proteins, can potentially generate neo-epitopes that are not only immunogenic but may also be pathogenic, activating some harmful pathways in the cascade of chronic central brain diseases induction or progression. The harmful activities of microbial transglutaminase may represent a new pathway in the gut-brain axis and might open new therapeutical strategies to fight neurodegenerative conditions.